2011
DOI: 10.1016/j.bone.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone 1 (1–34) acts on the scales and involves calcium metabolism in goldfish

Abstract: The effect of fugu parathyroid hormone 1 (fugu PTH1) on osteoblasts and osteoclasts in teleosts was examined with an assay system using teleost scale and the following markers: alkaline phosphatase (ALP) for osteoblasts and tartrate-resistant acid phosphatase (TRAP) for osteoclasts. Synthetic fugu PTH1 (1-34) (100 pg/ml to 10 ng/ml) significantly increased ALP activity at 6 h of incubation. High-dose (10 ng/ml) fugu PTH1 significantly increased ALP activity even after 18 h of incubation. In the case of TRAP ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Previously, we reported that parathyroid hormones first acted on osteoblasts at 6 hours of incubation and then activated osteoclasts at 18 hours of incubation via RANK/RANKL signaling (Suzuki et al, 2011a). Results similar to those of parathyroid hormones were obtained by prostaglandin E2 (Omori et al, 2012).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previously, we reported that parathyroid hormones first acted on osteoblasts at 6 hours of incubation and then activated osteoclasts at 18 hours of incubation via RANK/RANKL signaling (Suzuki et al, 2011a). Results similar to those of parathyroid hormones were obtained by prostaglandin E2 (Omori et al, 2012).…”
Section: Discussionsupporting
confidence: 68%
“…These goldfish were kept in the aquarium for 1 and 2 days (each n = 10). These experimental periods were adopted because hormonal and toxicological effects were influenced in goldfish during 2 days (Suzuki et al, 2004a;Suzuki et al, 2004b;Suzuki et al, 2011a;Omori et al, 2012;Yachiguchi et al, 2014b). During the experimental periods, these goldfish were fasted to exclude intestinal calcium uptake from diets.…”
Section: Effects Of Naf On Plasma Calcium Level In the Goldfish (In Vmentioning
confidence: 99%
See 1 more Smart Citation
“…In osteoblasts, also, both InHg and MeHg inhibited the ALP enzyme activity at 18 and 36 hrs after incubation. It is known that the scales are calcified tissue that contains osteoclasts and osteoblasts (Bereiter-Hahn and Zylberberg, 1993;Yoshikubo et al, 2005;Suzuki et al, 2007;Suzuki et al, 2008;de Vrieze et al, 2010;Suzuki et al, 2011a;Thamamongood et al, 2012, Yano et al, 2013. Additionally, it has been reported that scales are a better potential internal calcium reservoir than body skeletons, jaws, and otoliths examined by the 45 Calabeling study of calcified tissues of goldfish and killifish (Mugiya and Watabe, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…EF-1α (AB874605) was amplified using the following primers: sense: 5′-GTATGGTCGTCACCTTTGCTC-3′; antisense: 5′-GTGGGTCGTTCTTGCTGTC-3′. The PCR amplification was performed using the real-time Mx3000p PCR apparatus (Agilent Technologies, Santa Clara, CA, US) (Suzuki et al, 2011a). The annealing temperature of TRAP, COL1A1, MT, and EF-1α was 60°C.…”
Section: Changes In Trap Col1a1 and Mt Mrna Expression Of The Scalementioning
confidence: 99%